Prevalencia de síntomas asociados a trastornos musculoesqueléticos en estudiantes de práctica clínica facultad de Odontología Universidad Antonio Nariño (2023)
Dentistry requires postures and movements associated with musculoskeletal disorders of the body, presenting symptoms and disorders. Objective: to establish the prevalence of musculoskeletal symptomatology in students of clinical practice of the Faculty of Dentistry, UAN, Bogotá campus. Methodology: observational cross-sectional study; with a sample of 154 students in the period 2022-2, accepting informed consent and filling out the Kuorinka Nordic Questionnaire; students with traumas and pregnant women were excluded; data were recorded in Excel for analysis.